Carbohydrate and protein co-ingestion postexercise does not improve next-day performance in trained cyclists - Kontro, H.; Kozior, M.; Whelehan, G.; Amigo-Benavent, M.; Norton, C.; Carson, B. P.; Jakeman, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Supplementing postexercise carbohydrate (CHO) intake with protein has been suggested to enhance recovery from endurance exercise. The aim of this study was to investigate whether adding protein to the recovery drink can improve 24-hr recovery when CHO intake is suboptimal. In a double-blind crossover design, 12 trained men performed three 2-day trials consisting of constant-load exercise to reduce glycogen on Day 1, followed by ingestion of a CHO drink (1.2 g·kg-1·2 hr-1) either without or with added whey protein concentrate (CHO + PRO) or whey protein hydrolysate (CHO + PROH) (0.3 g·kg-1·2 hr-1). Arterialized blood glucose and insulin responses were analyzed for 2 hr postingestion. Time-trial performance was measured the next day after another bout of glycogen-reducing exercise. The 30-min time-trial performance did not differ between the three trials (M ± SD, 401 ± 75, 411 ± 80, 404 ± 58 kJ in CHO, CHO + PRO, and CHO + PROH, respectively, p = .83). No significant differences were found in glucose disposal (area under the curve [AUC]) between the postexercise conditions (364 ± 107, 341 ± 76, and 330 ± 147, mmol·L-1·2 hr-1, respectively). Insulin AUC was lower in CHO (18.1 ± 7.7 nmol·L-1·2 hr-1) compared with CHO + PRO and CHO + PROH (24.6 ± 12.4 vs. 24.5 ± 10.6, p = .036 and .015). No difference in insulin AUC was found between CHO + PRO and CHO + PROH. Despite a higher acute insulin response, adding protein to a CHO-based recovery drink after a prolonged, high-intensity exercise bout did not change next-day exercise capacity when overall 24-hr macronutrient and caloric intake was controlled.